Genetic diversity for leaf rust resistance in some bread wheat varieties - V.G. DUBEY; M.Y. SAMDUR, A.N. MISHRA*, K. KAUSHAL (Indian Phytopathology, 2010)
A study was conducted on the inheritance of seedling resistance to the leaf rust pathotype 77-5 (121R63-1) in five resistant varieties of bread wheat, namely, HP 1761, HS 365, HUW 468, PBW 498 and VL 832, as there is an urgent need to identify genetically diverse sources of resistance to this pathotype. Resistance in these genotypes is governed by a single dominant gene. Allelic tests revealed that HUW 468 and PBW 498 shared a common resistance gene which was different from each of the genes present in the other varieties. Thus, a total of four diverse genes were identified among the five varieties studied. The resistance gene in HP 1761 seems to be Lr9, based on the parentage and the characteristic low infection type. Though the identity of the other identified genes is not known, these appear to be either novel or at least different from the common ones among Indian bread wheat germplasm.